Relationship Between Daily Animal Protein Consumption with Anemia Status in Pregnant Women at the Masaran 1 Health Center - Anitha Kusumawati; Ratih Dwilestari Puji Utami; Wahyu Rima Agustin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
One of the hemodynamic problems due to the lack of adequate nutritional intake that is often experienced by pregnant women is anemia (Mariana, 2018). The incidence of anemia or lack of blood in pregnant women in Indonesia according to Riskesdas 2018 is 48.9%, with 84.6% of anemia occurring at the age of 15-24 years, at the age of 2534 by 33.7%, and by the age of 35-44 by 33.6%. The function of protein during pregnancy is as a means of transporting iron that will compose hemoglobin in the blood. Pregnant women with insufficient protein intake will experience anemia as much as 28.6% and the number of pregnant women who have good protein intake and not anemia will be 53.1%. The result of the bivariate analysis of the p-value value was .000. The value is less than 0.05 so it can be concluded that there is a relationship between daily animal protein consumption and anemia status in pregnant women at the Masaran I Health Center